The Restrictiveness of Business Services in the Visegrad Group - Myszkowska , Magdalena (Studia Oeconomica Posnaniensia, 2026)
The paper addresses the problem of regulations and provisions which restrict trade and investments in the business services sector within the countries of the Visegrad Group (V4). This is a significant issue on account of the growing role of business services as a key component of modern economies, as well as due to the fact that the position of V4 countries continues to strengthen on the global map of critical locations for this type of services. The research was carried out with the use of a descriptive method, on the basis of a data analysis of current regulations and provisions impacting international trade in services and restrictiveness indicators, originating from the new OECD Services Trade Restrictiveness Index database. The elaboration constitutes a contribution to further research on the relationship between the restrictiveness of service policy and international flows of services and goods.